2011
DOI: 10.1016/j.jeem.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

On the economics of energy labels in the housing market

Abstract: The residential housing market can play an important role in the reduction of global carbon emissions. This paper reports the first evidence on the market adoption and economic implications of energy performance certificates implemented by the European Union. The results show that adoption rates are low and declining over time, coinciding with negative sentiment regarding the label in the popular media. Labels are clustered among smaller, post-war homes in neighborhoods with more difficult selling conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
267
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(284 citation statements)
references
References 28 publications
15
267
1
1
Order By: Relevance
“…Buildings account for 40% of the energy consumption in Europe [1], and residential homes contribute to around one sixth of emissions globally [2]. Supplementary literature has begun to emerge on the willingness to pay for energy efficiency [3][4][5][6][7][8][9][10], whether energy savings are considered in buying decisions [11,12], and if financing should stem from private or public sources [13][14][15][16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Buildings account for 40% of the energy consumption in Europe [1], and residential homes contribute to around one sixth of emissions globally [2]. Supplementary literature has begun to emerge on the willingness to pay for energy efficiency [3][4][5][6][7][8][9][10], whether energy savings are considered in buying decisions [11,12], and if financing should stem from private or public sources [13][14][15][16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the environmental benefits and energy savings that can be gained from more energyefficient homes, evidence of buyer appreciation of the value of energy efficiency and domestic investment in efficiency measures to boost property values has been limited. Supplementary literature has begun to emerge on willingness to pay for energy efficiency (Banfi et al 2008;Brounen & Kok 2011;Cajias & Piazolo 2013;Cerin et al 2014; Department of Energy and Climate Change UK 2013; European Commission EC 2013a; Hyland et al 2013;McLean et al 2013;Popescu et al 2012), whether energy savings are considered in buying decisions (Amecke 2012;Murphy 2014), and if financing should stem from private or public sources (Allcot & Greenstone 2012;European Commission EC 2013b;Gillingham et al 2009Gillingham et al , 2012. This paper adds to this literature, providing hedonic value estimates for residential energy efficiency in the Dublin region of Ireland over the period 2009-2014.…”
Section: Introductionmentioning
confidence: 99%
“…Eichholtz et al (2013), Miller et al (2009), and Fuerst and McAllister (2011) show that green-certified buildings enjoy a premium on their rental prices and/or selling prices compared with similar non-certified buildings. Studies that analyze green buildings outside the United States have also found similar positive impacts of green certification on the economic values of buildings (Brounen and Kok 2010;Yoshida and Sugiura 2011).…”
Section: Introductionmentioning
confidence: 76%
“…Thus, another stream of literature analyzes the motives of buildings obtaining green certificates 2 and the diffusion patterns of green certificates. Using the data from Dutch housing market, Brounen and Kok (2010) run logit models on why some households apply for green certificates while others do not. They find that smaller and post-war homes have higher probability to adopt green certificates and that the adoption rates are positively correlated with the number of "green voters".…”
Section: Introductionmentioning
confidence: 99%